Integrating Tumor Sequencing Into Clinical Practice for Patients With Mismatch Repair-Deficient Lynch Syndrome Spectrum Cancers. Issue 8 (16th August 2021) - Dixon, Katherine; Asrat, Mary-Jill; Bedard, Angela C.; Binnington, Kristin; Compton, Katie; Cremin, Carol; Heidary, Nili; Lohn, Zoe; Lovick, Niki; McCullum, Mary; Mindlin, Allison; O'Loughlin, Melanie; et al.
Abstract : INTRODUCTION: Uninformative germline genetic testing presents a challenge to clinical management for patients suspected to have Lynch syndrome, a cancer predisposition syndrome caused by germline variants in the mismatch repair (MMR) genes or EPCAM . METHODS: Among a consecutive series of MMR-deficient Lynch syndrome spectrum cancers identified through immunohistochemistry-based tumor screening, we investigated the clinical utility of tumor sequencing for the molecular diagnosis and management of suspected Lynch syndrome families. MLH1-deficient colorectal cancers were prescreened for BRAF V600E before referral for genetic counseling. Microsatellite instability, MLH1 promoter hypermethylation, and somatic and germline genetic variants in the MMR genes were assessed according to an established clinical protocol. RESULTS: Eighty-four individuals with primarily colorectal (62%) and endometrial (31%) cancers received tumor-normal sequencing as part of routine clinical genetic assessment. Overall, 27% received a molecular diagnosis of Lynch syndrome. Most of the MLH1-deficient tumors were more likely of sporadic origin, mediated by MLH1 promoter hypermethylation in 54% and double somatic genetic alterations in MLH1 (17%). MSH2-deficient, MSH6-deficient, and/or PMS2-deficient tumors could be attributed to pathogenic germline variants in 37% and double somatic events in 28%. Notably, tumor sequencing could explain 49% of cases without causal germline variants, somatic MLH1 promoter hypermethylation, or somatic variants in BRAF . DISCUSSION: Our findings support the integration of tumor sequencing into current Lynch syndrome screening programs to improve clinical management for individuals whose germline testing is uninformative.